1990
DOI: 10.1139/y90-041
|View full text |Cite
|
Sign up to set email alerts
|

Conditioned taste aversion and motion sickness in cats and squirrel monkeys

Abstract: The relationship between vomiting and conditioned taste aversion was studied in intact cats and squirrel monkeys and in cats and squirrel monkeys in which the area postrema was ablated by thermal cautery. In cats conditioned 7 – 12 months after ablation of the area postrema, three successive treatments with xylazine failed to produce either vomiting or conditioned taste aversion to a novel fluid. Intact cats, however, vomited and formed a conditioned aversion. In squirrel monkeys conditioned 6 months after abl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 23 publications
2
22
0
Order By: Relevance
“…The fact that MFs can induce CTA learning is also consistent with activation of the vestibular system. Other studies have shown that vestibular stimulation (e.g., whole-body rotation) or labyrinthectomy can induce CTA (3,7,16,21,27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that MFs can induce CTA learning is also consistent with activation of the vestibular system. Other studies have shown that vestibular stimulation (e.g., whole-body rotation) or labyrinthectomy can induce CTA (3,7,16,21,27).…”
Section: Discussionmentioning
confidence: 99%
“…Exposure head-down toward the negative pole induced horizontal clockwise circling as viewed dorsally (25). Furthermore, we observed that when the MF exposure was paired with a novel taste solution (glucose ϩ saccharin), a conditioned taste avoidance (CTA) or aversion was induced similar to that seen after pairings of taste and rotation or motion sickness (3,7,16,21,25,27,37,44). At the neural level, MF exposure induced significant c-Fos immunoreactivity, a marker of neuronal activation, in specific vestibular and visceral nuclei within the rat brainstem (59).…”
mentioning
confidence: 99%
“…To date, there are no reports showing conditioned flavour aversion, using intra-oral infusion testing, in an emetic species. However, several studies show toxicosis-induced CFA in emetic species, including human, cat, dog, monkey, Suncus, and ferret (e.g., Jackson and Smith, 1978;Vavilova and Kassil, 1984;Rabin et al, 1986b;Fox et al, 1990;Rabin and Hunt, 1992;Smith et al, 2001a). These studies suggest a complex relation between a toxin's emetogenic potential and its potency to produce a CFA.…”
Section: Conditioned Flavour Avoidance (Cfa)-manymentioning
confidence: 99%
“…Area postrema has been implicated as a trigger zone for motion-induced emesis in the dog (Wang and Chinn, 1954) and monkey (Brizzee et al, 1980). However, more recent results are not as definite regarding its functional role (Borison and Borison, 1986;Wilpizeski et al, 1986;Sutton et al, 1988;Fox et al, 1990), and precisely how the area postrema affects vestibular reflex responses is still controversial (Jovanovic-Micic and Strbac, 1989;Gallo et al, 199 1). Interaction of the area postrema with other areas, for example, the solitary nucleus (Hay and Bishop,199 l), might be involved with homeostatic mechani ns controlling cardiovascular responses and electrolyte balance.…”
Section: Arsanilate Labyrinthectomymentioning
confidence: 99%